2007
DOI: 10.1002/ijc.22907
|View full text |Cite
|
Sign up to set email alerts
|

The E8 repression domain can replace the E2 transactivation domain for growth inhibition of HeLa cells by papillomavirus E2 proteins

Abstract: Continuous expression of the human papillomavirus (HPV) oncoproteins E6 and E7 is required for the growth of cervical cancer cell lines. So far, only the overexpression of the wild type papillomavirus E2 protein has been shown to induce growth arrest in HPV18-positive HeLa cells by repressing E6/E7 transcription. Growth arrest by E2 requires the aminoterminal transcription activation domain in addition to the carboxyterminal DNA-binding domain. Several papillomaviruses such as the carcinogenic HPV31 express in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 58 publications
5
39
0
Order By: Relevance
“…We recently demonstrated that 31E8^E2C is able to inhibit the growth of HeLa cells by binding to HPV promoter sequences and repressing the expression of the viral oncogenes E6 and E7 (38). To investigate whether the E8^E2C proteins of HPV16 and -18 also lead to growth arrest, HeLa cells were transfected with the pPur plasmid, providing puromycin resistance, and the eukaryotic expression vector pSG5 or derivatives expressing E8^E2C of HPV16, -18, or -31 in a 4:1 ratio.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that 31E8^E2C is able to inhibit the growth of HeLa cells by binding to HPV promoter sequences and repressing the expression of the viral oncogenes E6 and E7 (38). To investigate whether the E8^E2C proteins of HPV16 and -18 also lead to growth arrest, HeLa cells were transfected with the pPur plasmid, providing puromycin resistance, and the eukaryotic expression vector pSG5 or derivatives expressing E8^E2C of HPV16, -18, or -31 in a 4:1 ratio.…”
Section: Resultsmentioning
confidence: 99%
“…To be able to monitor the expression levels of the different E8^E2C and E2 proteins, HA epitopes were inserted internally in HPV16 and HPV18 E2 and E8^E2C genes as previously described for 31E2 and 31E8^E2C (38). HeLa cells were transfected with the empty vector or the respective expression vectors encoding the different E8^E2C or E2 proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations